2015
DOI: 10.1097/md.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Change of Both Endocrine and Exocrine Insufficiencies After Acute Pancreatitis in Non-Diabetic Patients

Abstract: Acute pancreatitis (AP) is the most common pancreatic disease and consists of an acute inflammation of the pancreas. AP can contribute to endocrine and exocrine insufficiencies in survivors as a result of the key role of the pancreas in both glucose metabolism and nutritional digestion. The aim of this population-based study was to determine the endocrine or exocrine insufficiencies in patients after initial AP with biliary or alcohol-associated causes.We conducted a nationwide cohort study using data from Tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 34 publications
5
53
2
8
Order By: Relevance
“…Recent studies have also indicated that PEI is much more common in acute pancreatitis (*21-29%) than previously thought, and that treatment with PERT can help to improve outcomes (reduced weight loss and flatulence, improved quality of life) [53,54]. Alcohol use and smoking are major factors in the development of acute pancreatitis and, together with the presence and extension of pancreatic necrosis, have been shown to correlate with the development of PEI [55]. PEI has been shown to be prevalent in approximately 87% of patients with autoimmune pancreatitis (AIP) [56].…”
Section: Prevalence Of Pancreatic Exocrine Insufficiency In Pancreatimentioning
confidence: 97%
“…Recent studies have also indicated that PEI is much more common in acute pancreatitis (*21-29%) than previously thought, and that treatment with PERT can help to improve outcomes (reduced weight loss and flatulence, improved quality of life) [53,54]. Alcohol use and smoking are major factors in the development of acute pancreatitis and, together with the presence and extension of pancreatic necrosis, have been shown to correlate with the development of PEI [55]. PEI has been shown to be prevalent in approximately 87% of patients with autoimmune pancreatitis (AIP) [56].…”
Section: Prevalence Of Pancreatic Exocrine Insufficiency In Pancreatimentioning
confidence: 97%
“…A large number of clinical and experimental researches suggest that, after AP, especially after SAP, endocrine and exocrine function of the pancreas often suffer varying degrees of damage, even developing permanent sequelae of pancreatic dysfunction [79]. Therefore, protecting acinar cell against necrosis in the early phase of AP would play a vital role in the pathological processes of AP.…”
Section: Introductionmentioning
confidence: 99%
“…During recovery from AP, pancreatic exocrine function is at a low level, causing PEI in some patients. PEI is commonly seen in alcoholic AP, severe acute pancreatitis (SAP), and AP with pseudocysts . About one‐third of the patients with SAP develop PEI, at a higher proportion compared with those with mild AP who develop PEI .…”
Section: Etiologymentioning
confidence: 99%